Microplastic Contamination in Fish, Water and Sediment from Milkfish Ponds: Environmental Insights from Kasemen District, Banten Province, Indonesia - Reza Mustika; Dodi Hermawan; Desy Aryani; Mas Bayu Syamsunarno; Riky Kurniawan (BRIN Publishing, 2025)
Plastic waste discarded into the environment can easily enter water bodies. One as such for an example is the milkfish farming ponds in Kasemen Subdistrict, which have become a dumping ground for household waste. This has led to the entry of plastic waste into the pond waters, which can be degraded into microplastics. This study aims to identify the content and abundance of microplastics in fish and other fish parts such as: flesh, intestines, stomach, gills, water, and sediment, as well as to measure the water quality in the milkfish farming ponds in Kasemen Subdistrict, Serang City, Banten Province. A total of 12 milkfish were collected from 6 stations, with 2 fish taken from each station using the random sampling method across 6 hectares of the farming ponds. The quantity and types of microplastics identified in the samples were analyzed using descriptive statistical analysis with software brand Meiji Techno. The results showed that the milkfish farming ponds in Kasemen Subdistrict were contaminated with microplastics, found in the fish's flesh, gills, intestines, stomach, water, and sediment. The microplastics identified were fiber, film, and fragment types. FTIR test results indicated that the microplastics found were made of polypropylene (PP) polymer.